Ta Det Onda Med Det Goda (Accepting the Bad that Comes with the Good) - A Cultural Framework for Identity Narratives of Difficult Experiences in Sweden. Issue 3 (2nd July 2020) - Eriksson, Py Liv; McLean, Kate C.; Frisén, Ann
ABSTRACT: This study investigates the nature of narrating experiences of difficult life events among Swedish young adults. We use the master narrative cultural framework to understand how narratives of difficult experiences are told. Building on extant work on the importance of the narration of difficult life events for identity and wellbeing, we examine how these stories are narrated in the Swedish context in relation to well-being. Identity narratives about life challenges were collected from 116 participants ( Mage = 33.28, SD = .54, n = 58 women). Employing an open-exploratory approach, four equally prevalent emotional sequences were found: redemptive sequencing, neutral/vague sequencing, a combination of positive and negative sequencing, and negative sequencing. No differences were found in the use of the first three emotional sequences for well-being, but the negative sequencing was generally associated with poorer well-being. This study shows that there are several ways to narrate difficult experiences in the Swedish context, and sheds light on how culture informs narrative identity.